Concurrent Malignant Solitary Fibrous Tumor Arising from the Omentum and Grade 3 Endometrial Endometrioid Adenocarcinoma of the Uterus with p53 Immunoreactivity - Naoya Harada; Ichiro Nobuhara; Noriko Haruta; Yumi Higashiura; Hideki Watanabe; Sumire Ohno (Hindawi Limited, 2014)
A malignant solitary fibrous tumor arising from the omentum is extremely rare. To our knowledge, this is the first case of a malignant solitary fibrous omentum tumor coexisting with uterine corpus cancer. A 62-year-old woman presented to our hospital with vaginal discharge. Endometrioid adenocarcinoma was diagnosed by endometrial curettage. In addition, a solid tumor in front of the uterus was detected following computed tomography and/or magnetic resonance imaging, which was suspected to be a primary (or secondary) malignant tumor arising from the omentum. Hysterectomy, bilateral salpingo-oophorectomy, omentectomy, and lymphadenectomy were performed. A malignant solitary fibrous tumor of the omentum and grade 3 endometrioid adenocarcinoma of the uterus were diagnosed by pathohistological analysis. Interestingly, the tumor cells were immunoreactive for p53. Adjuvant chemotherapy was administered for the uterine corpus cancer and the patient remains healthy 48 months after the surgery. These tumors may have become malignant due to the presence of p53 mutations.